Pandora hearts. 21 - Mochizuki, Jun (Yen Press, 2014)
"What I have granted them--is the "possibility" of survival. "I want you to be 'happy.'" One man's parting wish succeeds in awakening Oz's heart, long held captive in the depths of his own soul, as though breaking all the chains that bind him"--P. [4] of cover.